VIOLATING MAXIMS BY TOBA BATAK SELLERS AND BUYERS IN PARLUASAN TRADITIONAL MARKET PEMATANGSIANTAR - Desi Andani Manik; Rahmad Husein (State University of Medan, 2017)
The study deals with violating maxims by Toba Batak sellers and buyers in Parluasan traditional market. The objectives of the study are to find out the types of maxims are violated and to describe the implications of violating maxims by Toba Batak sellers and buyers in Parluasan Traditional Market Pematangsiantar.This research was conducted by using descriptive qualitative method. The data were the utterances between sellers and buyers from 30 conversations. The data were collected by recording the conversations. There were 117 utterances that violated the maxims used by Toba Batak sellers and buyers. The results showed that all types of maxim were violated; 58 utterances violated the maxim of quantity, 12 utterances violated the maxim of quality, 20 utterances violated the maxim of relation, and 27 utterances violated the maxim of manner. The implications of violating maxims that used by sellers and buyers were to show respect, to create hyperbole and irony, to change a topic, to keep a secret, and to create humors.